Management of zakat at the national amil zakat agency (Baznas) in Banjar City, West Java through data-based digitalization in era 4.0 - Hisam Ahyania; Fera Yuliani; Khodwi Parciska; Melania Martianingrum (Peneliti Teknologi Teknik Indonesia, 2022)
Industry 4.0 provides a transition process from analog format to digital format. The resulting data is digitized and can be used in a variety of ways. It aims to automate traditional manufacturing and industrial operations using newly developed information technology. The research methods used for data-based digitization in the management of zakat at the national zakat agency (BASZNAS) of Banjar City were observation, interview, and documentation. The Zakat Fund Management Mechanism was implemented through data archiving to ensure data security and the formation of a Zakat Management Unit (UPZ) to optimize BAZNAS’s activities. The distribution mechanism had been accomplished by providing Muslims with the convenience of paying Zakat through the implementation of trusted technology and administration.